Presentation of Financial Statements, Internal Control System, Accessibility of Financial Statements and Performance Audit on The Accountability of Regional Financial Management - Mardika Pramudianti; Wawan Sadtyo Nugroho (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to empirically test and analyze the effect of presentation of financial statements, internal control system, accessibility of financial statements and performance audit on the accountability of regional financial management. The research population is all regional organization in Magelang District. Based on the sampling method using purposive sampling, a sample of 26 regional organization in Magelang District. Hypothesis testing was performed using multiple linear regression analysis. The results showed that the presentation of financial statements had no effect on the accountability of regional financial management, internal control system had a positive effect on the accountability of regional financial management, accessibility of financial statements had no effect on the accountability of regional financial management and performance audit ad a positive effect on the accountability of regional financial management.